2019
DOI: 10.1002/jcp.28760
|View full text |Cite
|
Sign up to set email alerts
|

A novel long noncoding RNA FAF inhibits apoptosis via upregulating FGF9 through PI3K/AKT signaling pathway in ischemia–hypoxia cardiomyocytes

Abstract: Long noncoding RNAs (lncRNAs) have been increasingly considered to play an important role in the pathological process of various cardiovascular diseases, which often bind to the proximal promoters of the protein-coding gene to regulate the protein expression. However, the functions and mechanisms of lncRNAs in cardiomyocytes have not been fully elucidated. High-throughput RNA sequencing was performed to identify the differently expressed lncRNAs and messenger RNAs (mRNAs) between acute myocardial infarction (A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
24
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 37 publications
(48 reference statements)
2
24
0
Order By: Relevance
“…In recent years, studies have shown that lncRNAs play important roles in the progression of many diseases (24)(25)(26).…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, studies have shown that lncRNAs play important roles in the progression of many diseases (24)(25)(26).…”
Section: Discussionmentioning
confidence: 99%
“…One novel lncRNA FAF (FGF9-associated factor),verified by bioinformatics 66 , upon its overexpression could significantly inhibit ischemia-induced cardiomyocytes apoptosis. Knockdown of FAF could induced apoptosis.…”
Section: Lncrna Malat1mentioning
confidence: 97%
“…A specific analysis of lncRNAs involved in myocardial infarction has been performed by Chen and colleagues, which reports numerous studies aimed at performing high‐throughput screening of lncRNAs which are differentially expressed in various heart diseases 91 . They also report an implication for the lncRNAs ZFAS1, 92,93 HOTAIR, 94 MALAT1, 95,96 GAS5, 97 FAF, 98 TTTY15, 99 ECRAR, 100 AK080084, 101 NR_045363, 102 TUG1, 103 and Meg3 91,104 …”
Section: Lncrnas In Obesity‐associated Diseasesmentioning
confidence: 99%